Nexus between financial innovation and economic growth in South Asia: Evidence from ARDL and nonlinear ARDL approaches - Md. Qamruzzaman; Jianguo Wei (Financial Innovation, 2018)
This study examined the relationship between financial innovation and economic growth in Bangladesh, India, Pakistan, and Sri Lanka for the period Q1 1975 to Q4 2016. The autoregressive distributed lag (ARDL) bounds test was used to gauge long-run relationships, and the nonlinear ARDL (NARDL) test was used to explore asymmetry between financial innovation and economic growth in the sample of Asian countries. The findings from the bounds tests revealed long-run cointegration between financial innovation and economic growth in the sample countries. Furthermore, NARDL confirmed that positive changes in financial innovation linked positively with economic growth and vice versa in the long run. In the short run, however, the study found mixed behaviors in the case of positive and negative changes in financial innovation. To investigate directional causality, the Granger causality test under an error correction model was employed. The Granger causality results supported the feedback hypothesis in both the long run and short run. Thus, financial innovation boosts economic growth in the long run by stimulating financial service expansion, financial efficiency, capital accumulation, and efficient financial intermediation, which are essential for sustainable economic growth.
Keywords: O52; C21; 650; Financial innovation; Economic growth; ARDL; NARDL